THE EFFECT OF USING ACROSTIC POEM STRATEGY ON STUDENTS’ WRITING A POEM ABILITY AT THE ELEVENTH GRADE OF SMA NEGERI 1 SAYURMATINGGI IN 2020-2021 ACADEMIC YEAR - cristin enjelika hutabarat (JURNAL LINER (Language Intelligence and Educational Research), 2020)
Abstract: The aimed of this study to (a) describe of using acrostic poem strategy in teaching writing a poem. (b) Students’ writing a poem ability before and after using acrostic poem strategy. (c) Whether there was asignificant effect of using acrostic poem strategy at the eleventh grade of SMA Negeri 1 Sayurmatinggi. The study was conducted at the eleventh grade of SMA Negeri 1 Sayurmatinggi by applying experimental method (one group pretest posttest design). Sample of the study was 49 students and they were taken by using random sampling technique by applying slovin formulation. Instrument and test were used in collecting data. Based on descriptive analysis, the result showed (a) the average of using acrostic poem strategy was 3.6 (very good category) and (b) the average of students’ writing a poem before using acrostic poem strategy was 62.43 (enough category) and after using acrostic poem strategy was 86.7 (very good category). Furthermore, by using pair sample ttest (SPSS 22), the result showed the significant value was less than 0.05 (0.00<0.05). It means, there was any significant effect of using acrostic poem strategy on students’ writing a poem ability at the eleventh grade of SMA Negeri 1 Sayurmatinggi in 2020/2021 Academic Year. Keyword: Acrostic Poem Strategy , Writing a Poem Abstrak: Tujuan dari penelitian ini untuk (a) mendeskripsikan penggunaan strategi puisi akrostik dfalam pengajaran menulis puisi. (b) kemampuan siswa dalam menulis puisi sebelum dan sesudah menggunakan strategi puisi akrostik. (c) adakah pengaruh yang signifikan penggunaan strategi puisi akrostik pada siswa kelas XI SMA Negeri 1Sayurmatinggi. Penelitian dilakukan dikelas sebelas SMA Negeri 1 Sayurmatinggi dengan menerapkan metode eksperimen (one group pretest posttest design). Sampel dari penewlitian sebanyak 49 siswa dan diambil dengan menggunakan random sampling dengan memggunakan rumus slovin. Instrumen dan tes digunakan dalam pengumpulan data. Hasil penelitian menunjukan (a) rata-rata penggunaan strategi puisi akrostik 3.6 (kategori sangat baik) dan (b) rata-rata kemampuan siswa dalam menulis puisi sebelum meggunakan strategi puisi akrostik 62.43 (kategori cukup) dan rata-rata sesudah menggunakan strategi puisi akrostik 86.7 (kategori sangat baik). Selanjutnya dengan menggunakan uji pair sample ttest (SPSS 22) diperoleh bahwa hasil signifikan lebih kecil 0.05 (0.00<0.05). artinya ada pengaruh signifikan penggunaan strategi puisi akrostik terhadap kemampuan siswa dalam menulis puisi siswa kelas XI SMA Negeri 1 Sayurmatinggi tahun pelajaran 2020/2021. Kata kunci: strategi puisi akrostik, menulis puisi.